2020
DOI: 10.1370/afm.2500
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Use of the Fasting Algorithm for Singaporeans With Type 2 Diabetes (FAST) During Ramadan: A Prospective, Multicenter, Randomized Controlled Trial

Abstract: PURPOSE We aimed to evaluate the efficacy and safety of use of the Fasting Algorithm for Singaporeans with Type 2 Diabetes (FAST) during Ramadan. METHODS We performed a prospective, multicenter, randomized controlled trial. The inclusion criteria were age ≥21 years, baseline glycated hemoglobin (HbA 1c) level ≤9.5%, and intention to fast for ≥10 days during Ramadan. Exclusion criteria included baseline estimated glomerular filtration rate <30 mL/min, diabetesrelated hospitalization, and short-term corticostero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
(64 reference statements)
0
5
0
Order By: Relevance
“…Pharmacological therapies during Ramadan generated the most interest over the last year, with several new studies evaluating both oral and injectable diabetes therapies. [23][24][25][26][27][28][29][30][31] The studies included evaluations of individual drugs, targets, and professionals' perceptions [Table 2].…”
Section: Pharmacological Management Of Diabetes During Ramadanmentioning
confidence: 99%
See 2 more Smart Citations
“…Pharmacological therapies during Ramadan generated the most interest over the last year, with several new studies evaluating both oral and injectable diabetes therapies. [23][24][25][26][27][28][29][30][31] The studies included evaluations of individual drugs, targets, and professionals' perceptions [Table 2].…”
Section: Pharmacological Management Of Diabetes During Ramadanmentioning
confidence: 99%
“…Lum et al [24] evaluated the efficacy and safety of using the Fasting Algorithm for Singaporeans with T2D (FAST) during Ramadan in a prospective, multicenter, RCT. Participants were randomized to use of FAST or control (usual care without FAST) groups.…”
Section: Pharmacological Management Of Diabetes During Ramadanmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been found to improve glycaemic control with no major complications. [ 26 ] Empowering patients through these group- and individual-directed interventions could potentially improve their level of self-care for DM in the immediate and longer term. [ 27 ]…”
Section: Ramadan Monitoringmentioning
confidence: 99%
“…Several studies have shown that RF was associated with a positive impact in controlling blood glucose and weight loss among patients with T2D in adults (23)(24)(25). However, the findings of other studies suggested that RF could increase the risk of hypoglycaemia in some of these patients, while could not in others (26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%